1983
DOI: 10.3171/jns.1983.59.3.0439
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral circulation after head injury

Abstract: A considerable body of evidence suggests that posttraumatic disturbances of the cerebral circulation contribute to poor neurological outcome after blunt head injury, especially when regional cerebral blood flow (rCBF) falls to the ischemic range (below 17 ml/100 gm/min). Cerebral infarction concentrated in the arterial boundary regions has been described in patients who died. Since arterial boundary zones are the cortical areas most susceptible to cerebral ischemia, the authors have investigated the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Furthermore, more recently it has become clear that there are differences in the autoregulation curve between different hypotensive drugs, with nitroprusside (NTP) being associated with the greatest leftward shift on the curve (Stoyka and Schutz, 1975;Michenfelder and Theye, 1977;Maekawa, MtDowall and Okuda, 1979). \ Autoregulation is often impaired in areas of brain pathology, for example around traumatic brain contusions, tumours and in areas of cerebral vasospasm (Palvogyi, 1969;Overgaard and Tweed, 1974;Enevoldsen and Jensen, 1978). In such cases, cerebral perfusion decreases with any reduction in arterial pressure and it has been suggested that critically low perfusion may occur at greater arterial pressures in the absence of autoregulation.…”
mentioning
confidence: 99%
“…Furthermore, more recently it has become clear that there are differences in the autoregulation curve between different hypotensive drugs, with nitroprusside (NTP) being associated with the greatest leftward shift on the curve (Stoyka and Schutz, 1975;Michenfelder and Theye, 1977;Maekawa, MtDowall and Okuda, 1979). \ Autoregulation is often impaired in areas of brain pathology, for example around traumatic brain contusions, tumours and in areas of cerebral vasospasm (Palvogyi, 1969;Overgaard and Tweed, 1974;Enevoldsen and Jensen, 1978). In such cases, cerebral perfusion decreases with any reduction in arterial pressure and it has been suggested that critically low perfusion may occur at greater arterial pressures in the absence of autoregulation.…”
mentioning
confidence: 99%